Research on the Vulnerability of the Community to Flood: A Case Study at the Downstream of Gianh River, Quang Binh Province - Thi Ha Thanh, Nguyen; Ngoc Diep, Nguyen; Huu Duy, Nguyen; Dinh Kha, Dang; Le Tuan, Pham; Ngoc Tu, Bui (VNU Journal of Science: Earth and Environmental Sciences; Vol 37 No 4, 2021)
Flood is a frequent natural disaster which has a negative impact on the socio-economic activities of the community in the lower Gianh river area - one of the most vulnerability areas under the flood in the North Central Region, Vietnam. The aim of this paper is to assess the risk of flooding in the study area as well as point out the factors that increase the vulnerability of the local community. The study applies UNESCO-IHE vulnerability approach, combining the flood risk assessment method by MIKE FLOOD model and sociological investigation, with 90 household questionnaires (selected randomly and  door-to-door interview). The main results include flood risk level maps (by analyzing inundation depth and flood flow velocities); data on community resilience to flood (resilience capacity and local people's perceptions on flood risks). These results are the basis for not only raising awareness about flood risks but also propose non-structural flood protection solutions for managers and local communities in the research areas.